2019
DOI: 10.1055/s-0039-1692164
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities to Improve the Clinician Experience Reviewing Electronic Progress Notes

Abstract: Background High-quality clinical notes are essential to effective clinical communication. However, electronic clinical notes are often long, difficult to review, and contain information that is potentially extraneous or out of date. Additionally, many clinicians write electronic clinical notes using customized templates, resulting in notes with significant variability in structure. There is a need to understand better how clinicians review electronic notes and how note structure variability may impact clinicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…One participant voiced this discontent particularly saliently, saying “Most of my work does not feel like I'm working as a doctor but more like a secretary.” To cope with this documentation burden and spread of information, observed physicians would often copy and paste previous information into their current notes, possibly limiting the impact of new information; copy/paste and “note bloat” problems are a well-known symptom of EHR use. 50 51 52 These findings could suggest that differences in regulations regarding documentation between different countries, while undoubtedly a major factor, might not be the primary driver of dissatisfaction with EHRs in general and documentation in particular, as has been suggested previously. 53…”
Section: Discussionsupporting
confidence: 51%
“…One participant voiced this discontent particularly saliently, saying “Most of my work does not feel like I'm working as a doctor but more like a secretary.” To cope with this documentation burden and spread of information, observed physicians would often copy and paste previous information into their current notes, possibly limiting the impact of new information; copy/paste and “note bloat” problems are a well-known symptom of EHR use. 50 51 52 These findings could suggest that differences in regulations regarding documentation between different countries, while undoubtedly a major factor, might not be the primary driver of dissatisfaction with EHRs in general and documentation in particular, as has been suggested previously. 53…”
Section: Discussionsupporting
confidence: 51%
“…However, little is known about how resident physicians' EHR usage specifically, or how it changes as they gain experience. [18][19][20][21] Residents may face a large EHR time burden as they attempt to quickly learn multiple systems at once, or it may be the case that young, technologically savvy residents are efficient in the EHR and are able to minimize their after-hours time. 22 While recent studies have shown variation across physician specialty, 23 there is little evidence to date about how physician EHR usage varies by experience or changes over time as they become more facile with the system.…”
mentioning
confidence: 99%
“…For example, simply having clinical notes organized consistently can minimize the time clinicians spend reviewing them. 47 Interoperability of EHR systems (e.g., data collected from different health care institutions) is also an important factor to consider when looking at designing an EHR search function. If the search function can mine both data collected within the native-EHR system and data collected in another system, it may be useful to differentiate between those different data types when provided search results to users.…”
Section: Discussionmentioning
confidence: 99%
“…For example, simply having clinical notes organized consistently can minimize the time clinicians spend reviewing them. 47 …”
Section: Discussionmentioning
confidence: 99%